การบริหารทรัพยากรมนุษย์กับรูปแบบความผูกพันต่อองค์การของบุคลากรโรงเรียนสาธิต ในจังหวัดนครปฐม - มณีรัตน์, สุคนธ์; เจนอักษร, นพดล (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อทราบ 1) การบริหารทรัพยากรมนุษย์ของโรงเรียนสาธิตในจังหวัดนครปฐม 2) รูปแบบความผูกพันต่อองค์การของบุคลากรโรงเรียนสาธิตในจังหวัดนครปฐม และ 3) ความสัมพันธ์ระหว่างการบริหารทรัพยากรมนุษย์กับรูปแบบความผูกพันต่อองค์การของบุคลากรโรงเรียนสาธิตในจังหวัดนครปฐม การวิจัยครั้งนี้เป็นการวิจัยเชิงพรรณนา (descriptive research) ผู้ให้ข้อมูลคือ ผู้บริหารโรงเรียน บุคลากรสายผู้สอน และบุคลากรสายสนับสนุน จำนวน 79 คน จากโรงเรียนสาธิตในจังหวัดนครปฐม เครื่องมือที่ใช้ในการวิจัย เป็นแบบสอบถามเกี่ยวกับการบริหารทรัพยากรมนุษย์ ตามแนวคิดของเบอร์นาดิน (Bernadine) และความผูกพันต่อองค์การ ตามแนวคิดของคอลควิท ลีปายน์ และเวสสัน (Colquitt,Lepine and Wesson) สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ ความถี่ ร้อยละ ค่ามัชฌิมเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน ค่าสัมประสิทธิ์ สหสัมพันธ์ของเพียร์สัน ผลการวิจัยพบว่า 1. การบริหารทรัพยากรมนุษย์ของโรงเรียนสาธิตในจังหวัดนครปฐม โดยภาพรวมและรายด้านอยู่ในระดับมาก โดยเรียงค่ามัชฌิมเลขคณิตจากมากไปหาน้อยคือ การจัดหาบุคคลเข้าทำงาน การจัดรูปแบบองค์การ การฝึกอบรมและการพัฒนาการบริหารผลการปฏิบัติงาน รางวัลและสิทธิประโยชน์ 2. รูปแบบความผูกพันต่อองค์การของบุคลากรโรงเรียนสาธิตในจังหวัดนครปฐม โดยภาพรวมและรายด้านอยู่ในระดับมาก โดยเรียงค่ามัชฌิมเลขคณิตจากมากไปหาน้อยดังนี้คือ ความผูกพันทางความรู้สึก ความผูกพันที่เป็นปทัสถาน ความผูกพันแบบต่อเนื่อง 3. ความสัมพันธ์ระหว่างการบริหารทรัพยากรมนุษย์กับรูปแบบความผูกพันต่อองค์การของบุคลากรโรงเรียนสาธิต ในจังหวัดนครปฐม มีความสัมพันธ์กันอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 THE HUMAN RESOURCE MANAGEMENT AND ORGANIZATIONAL COMMITMENT TYPE OF DEMONSTRATION SCHOOL PERSONNEL IN NAKHON PATHOM PROVINCE This research aimed to investigate 1) the human resource management in the demonstration schools in Nakhon Pathom province, 2) the organizational commitment type of the demonstration school personnel in Nakhon Pathom province, and 3) the relationship between human resource management and organizational commitment type of demonstration school personnel in Nakhon Pathom province. This study was a descriptive research. The respondents were administrators, teachers and supporting staff in demonstration schools in Nakhon Pathom province, 79 respondents in total. The research instrument was a questionnaire concerning human resource management according to the concept of Bernadine and organizational commitment type according to the concept of Colquitt, Lepine and Wesson. Statistics used in this research were frequency, percent, arithmetic mean, standard deviation, and Pearson’s Correlation Coefficient. The research findings were as follows: 1 The human resource management in the demonstration schools in Nakhon Pathom province, overall and each aspect, was found at the high level, ranking from the highest mean to the lowest mean as follow : recruiting, organizing, training and development, performance appraising, and rewards and benefits, respectively. 2. The organizational commitment type of the demonstration school personnel in Nakhon Pathom province, overall and each aspect, was found at the high level, ranking from the highest mean to the lowest mean as follow : affective commitment, normative commitment, and continuance commitment respectively. 3. The relationship between the human resource management and the organizational commitment type of the demonstration school personnel in Nakhon Pathom province was found at .01 level of statistical significance.